El cómic, una estrategia pedagógica que fortalece el pensamiento crítico en el aprendizaje de las ciencias sociales, para los estudiantes del Liceo Español Pérez Galdós - Guarnizo Gordillo, Adriana Patricia (Universidad Antonio Nariño, 2021)
This research work seeks to actively and constantly implement the use of comics, as a pedagogical strategy, for the teaching and learning of Social Sciences, in ninth grade students of the Pérez Galdós Spanish High School. In order to enhance the capacity for critical thinking through the image, analysis, interpretation and construction of comics. This monograph is supported by the Participation Action Research approach, which made it possible to use different data collection instruments and carry out the phases designed to strengthen critical thinking and an autonomous position of students, with respect to social realities that they are presented from their close and immediate contexts. The results indicate that the students order their thoughts sequentially, enhancing their ideas and imagination, developing the skills and social competencies that human beings need.